O processo de construção de políticas de inclusão social no projeto Escola Cabana: consensos e tensionamentos entre os segmentos sociais e o poder público municipal - OLIVEIRA, Izabel Cristina Borges Corrêa (2007)
This study about The building process of politics of social inclusion in the Cabana School project and the consensus and the tensions between social segments and the public government of the city looked for investigate and reflect if this project made possible (or not) the inclusion and participation of social segments (womens movement, homosexuals, black people and PNEEs), and the contemplation of their claims and interests in the process of public politics formularization and elaboration, from official documents analysis, speaking of social movements integrants and school leaders of the city, in the period from 1997 to 2000, and from 2001 to 2004. It embraces a discussion about understanding perspectives related to social inclusion and exclusion, democratized public spaces, popular participation and identities processes, having as background the boarding of Brazils redemocratization period. This study appreciated the relation between documents produced by the city government about Cabana School project and the interviewers testimonies, establishing series of variables which acquit motivations of society in the involvement with social segments, and managers of the public power with social civil entities during the writing of the related project. It verifies, from the research, that public politics materialized in consequence of interactions between public administration of the city and the movements showed different articulations, with consensual basis evidences, but with intense conflicts, tensions and some difficulties. The discussion emphasizes the relevance of this experience to Belém and other cities as a viable opportunity to participate and to use public spaces by popular sectors. It discloses that, although the possibilities of creating alternatives of innovative character, the existing proposals which aim the elimination of social exclusion contexts and the configuration of identities processes, the project was jeopardized by managers inexperience, by the partial appropriation of determined social sectors, and its legal informality.